KEPERCAYAAN DIRI DALAM PEMILIHAN KARIR DITINJAU DARI DUKUNGAN SOSIAL ORANG TUA PADA REMAJA AKHIR DI YOGYAKARTA - Nur Aini, Ani; Malahati, Fildzah (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Self-confidence in career choice in late adolescents is influenced by several factors, one of which is environmental factors in the form of parental social support. This study aims to determine the relationship between parental social support and self-confidence in career choice in late adolescents. The research method used is a correlational quantitative approach using accidental sampling technique. The sample taken was 110 who were late adolescents aged 18-24 years in Yogyakarta. Data collection using self-confidence scale in career choice and parental social support. The results of data analysis of this study indicate that there is a positive correlation result of 0.769 with sig = 0.000 (p <0.05) which can be concluded that there is a significant positive relationship between parental social support and self-confidence in career selection, assuming that the higher the level of parental social support, the higher the self-confidence in career selection. Conversely, if the lower the level of parental social support, the lower the confidence in career choice.